2020
DOI: 10.29392/001c.17604
|View full text |Cite
|
Sign up to set email alerts
|

Towards the scale and menace of unregulated sonography practice in Ghana

Abstract: Background Background There is a high demand for medical sonographers, mainly due to high antenatal and other ultrasound examinations. Ghana has 334 registered radiographers and sonographers for a population of 30 million. The non-existence of strict enforcement of mandatory credentialization and licensure for the practice of ultrasonography has made the proliferation by quacks very pervasive in Ghana. However, there is inadequate knowledge about the activities of these unlicensed sonographers. This paper look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This study also reported the availability of MRI in the country [9]. However, there is an increased use of ultrasound equipment because it is the first-line imaging modality for the diagnosis of uterine fibroids and pregnancy, as it is inexpensive, easier to use, very portable and clearly provides adequate features for the diagnosis of uterine fibroids [10][11][12].…”
Section: Introductionmentioning
confidence: 65%
“…This study also reported the availability of MRI in the country [9]. However, there is an increased use of ultrasound equipment because it is the first-line imaging modality for the diagnosis of uterine fibroids and pregnancy, as it is inexpensive, easier to use, very portable and clearly provides adequate features for the diagnosis of uterine fibroids [10][11][12].…”
Section: Introductionmentioning
confidence: 65%
“…The Royal College of Radiologists (RCR) and the Society and College of Radiographers (SCoR) of the United Kingdom (UK) emphasize the importance of ensuring high-quality interpretation of ultrasound 4,5 examinations for patients. Ultrasound imaging is heavily reliant on the skills of the operator, which 2,3 require time and experience to develop.…”
Section: Figure 1 Ultrasound Machine At a Public Hospital In Zimbabwementioning
confidence: 99%
“…Sixteen percent (16%) of ultrasonographers in Ghana are not licensed despite the existence of regulatory bodies for licensure. Despite the existence of ultrasound practice in eleven (11) out of sixteen (16) regions in the country, there is still an unfair distribution of sonographers because 70% of them are located in the Greater Accra-and Ashanti regions. 11 There has been a marked improvement in the acquisition of CT facilities in Ghana currently compared with the early 90s, while MRI equipment acquisition has witnessed only a marginal increase of 1, i/e.…”
Section: Achievements/observationsmentioning
confidence: 99%